(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Some data on the distribution and the ethology of Hymenoptera Bombidae are known in Italy, but there are scarse information on the morphology and the classification of these important pollinators. To make a contribution to this subject, the structure of the male genitalia of Bombus Latr., which is necessary for the construction of specific taxonomici keys, is illustrated through a comparison of the opinions of different Authors. In addition, the male genitalia and some notes on the colours of B. hortorum (L.), pascuorum (Scop.), ruderarius (Muller), lapidarius (L.), magnus Vogt, pratorum (L.), soroeensis (Fabr.), terrestris (L.) are described.